EL CRECIMIENTO COMERCIAL DE LAS FRANQUICIAS Y SU INCIDENCIA EN LA ECONOMIA DE LA CIUDAD DE TRUJILLO – LA LIBERTAD - Chirinos Cueva, Giancarlo Nicolas (2015)
The present research work aims to determine the influence of franchises in the economy of Trujillo. The research problem is referred to the following question: the commercial growth of franchises has an impact on the economy of the city of Trujillo?, which hypothesis is: the commercial growth of the franchise positively affects the economy of the city of Trujillo, stressing as study variables: independent Variable: commercial growth of franchises.; and the dependent variable: economy of the city of Trujillo. The population for this research will be represented by companies that operate under the franchise system were determined 13 franchises in the city of Trujillo, among the main we have KFC and Starbucks. The considered sample for this research is a company in the field Cafe - patisserie, choosing this turn in order to know and evaluate the possibility of installation of any franchise in the rotation, since according to the research carried out there are few existing in the city of Trujillo companies that perform their work under a franchise of the giro Café - pastry , and is a great investment opportunity. Enterprises taken as sample is the franchise for Starbucks and Juan Valdez, are chosen for the following reasons: As the most representative in the bakery business - Café. Because they have a variety of products. For permanence in the local market, since 2010. The ease of access to information. The companies are better organized. They also have their information better channelled, allowing you to carry out the investigation. The design of transverse descriptive investigation, as well as inductive methods; analytical, statistical and research technique of data, as the survey and personal interview. According to the results, we can say that the commercial growth of franchises influences in the economy of the city of Trujillo, by increases in the figures and in employment rates, for the category of services, investment and spending per capita among others.